2012
DOI: 10.1007/s10958-012-1102-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimal heuristic algorithms for the image of an injective function

Abstract: The existence of optimal algorithms is not known for any decision problem in NP \ P. We consider the problem of testing the membership in the image of an injective function. We construct optimal heuristic algorithms for this problem in both randomized and deterministic settings (a heuristic algorithm can err on a small fraction 1 d of the inputs; the parameter d is given to it as an additional input). Thus for this problem we improve an earlier construction of an optimal acceptor (that is optimal on the negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A distributional problem is a pair of a language L and an ensemble of distributions D. A heuristic proof system [7] for a distributional problem (L, D) is an algorithm Π(x, w, δ; n) such that the following properties are satisfied:…”
Section: Heuristic Proofsmentioning
confidence: 99%
“…A distributional problem is a pair of a language L and an ensemble of distributions D. A heuristic proof system [7] for a distributional problem (L, D) is an algorithm Π(x, w, δ; n) such that the following properties are satisfied:…”
Section: Heuristic Proofsmentioning
confidence: 99%
“…In a parallel work [HINS11], we define simulations on the average in a different way: while Definition 4.2 is designed so that Levin-style Definition 4.1 of average-case polynomiality is closed under these simulations, the definitions of [HINS11] are intended to work with Impagliazzostyle average-case polynomiality [Imp95].…”
Section: Optimality On the Averagementioning
confidence: 99%
“…It was proved that for the language of Boolean tautologies, an optimal acceptor exists if and only if a p-optimal proof system exists; Messner generalized this result to paddable languages [Mes99]. While it is easy to see that Messner's proof goes for randomized acceptors as well, it does not apply to computations with advice (where optimal proof systems exist [CK07], but no optimal acceptors are known), heuristic computations (where optimal acceptors do exist [HINS11], but no optimal proof systems are known), or the restricted notion of optimality used in this paper. Recently, it was shown that the existence of optimal acceptors is equivalent for all co -NP-complete languages [CFM11].…”
Section: Introductionmentioning
confidence: 99%
“…Approximate algorithms are able to find good answers (near to optimal solutions) for NP-hard in a short time. They are divided into two groups of heuristic algorithms [8][9][10] and meta-heuristic algorithms [11]. Heuristic approaches create suitable and good solutions which normally are not the best solution.…”
Section: Introductionmentioning
confidence: 99%